Removal of Manganese in Contaminated Groundwater by Permeable Reactive Barriers Using Compost and Zero Valent Iron - Wilopo, Wahyu; Putra, Doni Prakasa Eka (2014)
SoTtion ard frccipilation of nungatrcse in grouodwater rclnediation Llsillg conrposl rnrl Tero valcnl irolr (ZVI) werc investjgalcd bl batch and colunm cxperirrcnts. In batcl tcsrs. cornpost rs orore cffcclile than Z\rl to irxnobilizc nungaDese, wiih the maximum rirmo\,.1l of 23E.09 mnrol Mn. kg I of compo-* accorrling to l-angmuir equa{ion- High clfioieDcv of I\,ln re,roval onro conlpost is brobably nol onl) b_lr physical sorplion bur aiso by sur-ticc complexaiion \\,i1h carbo\ylic gr;ups in the corrrpost. Tlris rcsult \\,as confinred with FTIR data thri sho\u ne$. peaks at (,7i cmi alter conlacted witll nrangancsc solution. I\,langaoesc was also inmobilizcd lirough soqrlion onto ZVI due to high srLfacc area, a d parlly b), precipirarion rs miinganese oxidc because of intense alkalization. In columrl atedals_ aftcr introduciog mangancse solution lor l6 porc yolumes (p\J. lnaDsaocsc rvas prcdominanll], irnnrobilized in uppcr p.rlt of the coluuri. it is corlsidered rhal composl \\ias degradcd and rhc sufxce ofZVl gaDulcs was alrcadv unilblntcd and conosion producls xre thc nlost accumulatcd on Z\,1 E.rnuL." nerr ih( inlet hecJr"t ZvI |.1s bcen cortactc{] wiih high concentrations ollnanlllnese fbr the longesi timc in the ost botlorn pans. This \!as aiso suppci€d by XRir data liom ZVI grains that Dtatganese was Lhe larecsr in the mosl bottom segmenl. 1he results ofgeochcnrical calc0lrtiu|\ alon3 (irh rhe Sl:M ina!< suggc"r that pa ly ol maoganese $crc also prccipitared wifi cxrbonates. The result dcnxmsn.aics thal combi llliorr of conrpost and ZVI is more elicclivc 1() ielrovc nungancsc thnn using single marcrial duc to thc dillercnt nrecbanism olremoval lioDt cacil material.